Sex differences in anthropometric characteristics, Motor and cognitive functioning in preschool children at the time of school enrolment - Bala, Gustav (Array, 2009)
Abstract: The study included a sample of 333 preschool children (162 male and 171 female) at the time of school enrolment. Study subjects were recruited from the population of children in kindergartens in the cities of Novi Sad, Sombor, Sremska Mitrovica and Ba~ka Palanka (Province of Voivodina, Serbia). Eight anthropometric variables, seven motor variables and one cognitive variable were analyzed to identify quantitative and qualitative sex differences in anthropometric characteristics, motor and cognitive functioning. Study results showed statistically significant sex differences in anthropometric characteristics and motor abilities in favor of male children, whereas no such difference was recorded in cognitive functioning. Sex differences found in morphological and motor spaces contributed to structuring proper general factors according to space and sex. Somewhat stronger structures were observed in male children. The cognitive aspect of functioning yielded better correlation with motor functioning in female than in male children. Motor functioning correlated better with morphological growth and development in male children, whereas cognitive functioning was relatively independent. These results are not fully in accordance with the current concept of general conditions in preschool children, nor they fully confirm the theory of integral development of children, hence they should be re-examined in future studies. Although these study results cannot be applied to sports practice in general, since we believe that it is too early for preschool children to take up sports and sport competitions, they are relevant for pointing to the need of developing general motor ability and motor behavior in preschool children